Sulfoxide Reductases and Applications in Biocatalytic Preparation of Chiral Sulfoxides: A Mini-Review - Peng, Tao; Cheng, Xiaoling; Chen, Yongzheng; Yang, Jiawei (Frontiers in Chemistry, 2021)
Chiral sulfoxides are valuable organosulfur compounds that being widely used in medicinal and organic synthesis chemistry. Biocatalytic approaches for the preparation of chiral sulfoxides were developed in past few years, mainly through asymmetric oxidation of prochiral sulfides. Recently, application of sulfoxide reductase to prepare chiral sulfoxides through kinetic resolution has emerged as a new method, exhibiting excellent catalytic properties. This paper reviews the finding, chemistry and biological function of these sulfoxide reductases and highlights their applications in chiral sulfoxide preparation.